2020
DOI: 10.3389/fsurg.2020.00018
|View full text |Cite
|
Sign up to set email alerts
|

Manometry of the Human Ileum and Ileocaecal Junction in Health, Disease and Surgery: A Systematic Review

Abstract: Background: The terminal ileum and ileocaecal junction form a transition zone in a relatively inaccessible portion of the gastrointestinal tract. Little is known about the motility of this region with few detailed studies, indicating the need for a robust synthesis of current knowledge. This review aimed to evaluate the quantitative and qualitative data on the manometry findings of the terminal ileum and ileocaecal junction during the fasting and post-prandial periods in healthy individuals and patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
(212 reference statements)
0
7
0
Order By: Relevance
“…While this increase is modest, this amount of liquid can be expected to significantly increase distension of the ascending colon whose resting volume averages 203 mL. 43 The rapid fall in SBWC after feeding a large second meal is novel but in keeping with previous observations made using a range of techniques including barium, 8 intestinal perfusion, 44 manometry, 45 and scintigraphy. 46 The manometric studies have reported a rapid cessation of fasting patterns after eating, with increased ileal motility lasting at least 2 hours, some of the patterns being propulsive.…”
Section: Comparison Of Solutions Of Simple Sugars With Fatty Emulsionsmentioning
confidence: 68%
See 1 more Smart Citation
“…While this increase is modest, this amount of liquid can be expected to significantly increase distension of the ascending colon whose resting volume averages 203 mL. 43 The rapid fall in SBWC after feeding a large second meal is novel but in keeping with previous observations made using a range of techniques including barium, 8 intestinal perfusion, 44 manometry, 45 and scintigraphy. 46 The manometric studies have reported a rapid cessation of fasting patterns after eating, with increased ileal motility lasting at least 2 hours, some of the patterns being propulsive.…”
Section: Comparison Of Solutions Of Simple Sugars With Fatty Emulsionsmentioning
confidence: 68%
“…46 The manometric studies have reported a rapid cessation of fasting patterns after eating, with increased ileal motility lasting at least 2 hours, some of the patterns being propulsive. 45 The scintigraphic studies showed that the rate of emptying of the terminal ileum is increased following a meal and enhanced by guar gum. 46,47 This presumably reflects increased flow secondary to water trapping by guar.…”
Section: Comparison Of Solutions Of Simple Sugars With Fatty Emulsionsmentioning
confidence: 99%
“…One of the major advantages using the wireless capsule device in GI investigations is that the capsule can reach inaccessible areas of the GI tract, such as ileocecal junction (ICJ) 27,28 . Because of the relative inaccessibility, only a few manometry studies have been done in the terminal ileum and across the ICJ 29–32 . However, by using the combi‐unit, the contractility of the ICJ region can be quantified as it traverses from the ileum to ascending colon.…”
Section: Discussionmentioning
confidence: 99%
“…in the terminal ileum and across the ICJ. [29][30][31][32] However, by using the combi-unit, the contractility of the ICJ region can be quantified as it pulsive properties and motility transmission of the terminal ileum in humans, 30,31 and showed that contraction patterns from the terminal ileum, across the ICJ, and into the cecum can be recorded physiologically. To further explore the functional specialization of the ICJ, the ICJ should be considered as having properties that are determined not only by its anatomy and function, but also by coordination of motility and contractility in the adjacent distal ileum and proximal colon.…”
Section: Contractions and The Combi-unit Movements In The Lower Gi Tractmentioning
confidence: 99%
“…A recent systematic review on motility patterns in the terminal ileum has been conducted and shows differences in motility patterns in the fasted and fed states [230]. In healthy individuals in the fasted state the mean duration of phase III of the MMC ranged from 6.5-18.8 minutes; the mean propagation velocity (for the phase III MMC) was 0.3-3.1 cm*min -1 and the frequency of contractions was 8.0-11.9 per minute [230].…”
Section: Small Intestinal Motilitymentioning
confidence: 99%